El reto de la seguridad de los Centros de Justicia Penal Federal en México ante el Nuevo Sistema Penal Acusatorio y el Crimen Organizado - Tovar Cruz, Nadia (Hemisferio - Revista del Colegio Interamericano de Defensa, 2018)
This document aims to generate for the reader an integral vision from the security perspective of the implications of an oral trial in front of the main leaders of the cartels in Mexico. The New Adversarial System represents one of the greatest challenges in terms of its implementation, since it represents a paradigm shift in the prosecution of crimes and in the delivery of justice in this country. This topic is particularly relevant when one analyzes it in the context of a security crisis detonated by the growth and empowerment of organized crime, which has co-opted many government structures and society itself.